Image analysis : a new method for estimating triploidy in commercial bivalves - Gerard, Andre; Naciri, Yamama; Peignon, Jean-marie; Ledu, Christophe; Phelipot, Pascal; Noiret, Christophe; Peudenier, Isabelle; Grizel, Henri (1994)
For determination of ploidy levels in bivalves, three techniques are now routinely used: karyological determination. microfluorimetry and flow cytometry. This paper proposes an alternative technique which is based on determination of the optical density (OD) of stained nuclei using image analysis. A karyological and image analysis comparative experiment conducted on juveniles of Crassostrea gigas (Thunberg) and Ruditapes philippinarum (Adam & Reeve) is described and highlights the advantages of the image analysis technique. Initially developed on C. gigas and R. philippinarum, the image analysis method was easily extended to other bivalve species and to different developmental stages, as demonstrated by two experiments conducted on Ostrea edulis (L.). First, percentage of triploids was consistent from the D-larval to the adult stage of development, despite the use of different preparation techniques depending on the stage examined. Second, a rise in ploidy percentage demonstrated a differential mortality between diploid and triploid animals. Image analysis techniques arc cheaper than flow cytometry but more expensive than microfluorimetry. However, image analysis equipment can also be used for algae, eggs and spermatozoa counting, and other purposes such as fluorescence measurements, analysis of autoradiographs and electropharesis gels, and measurement of immuno-histochemical reactions.